Uncovering Environmental Change in the English Lake District: Using Computational Techniques to Trace the Presence and Documentation of Historical Flora. - Smail, Robert; Donaldson, Chris; Govaerts, Rafaël; Rayson, Paul; Stevens, Carly (Digital Scholarship in the Humanities, 2021)
There is a lack of concrete knowledge about floristic change in Britain before the mid-20th century. Relevant evidence is available, but it is principally contained in disparate historical sources. In this article, we demonstrate how such sources can be efficiently collated and analysed through the implementation of state-of-the-art computational-linguistic and historical-geographic information systems (GIS) techniques. We do so through a case study that focuses on the floristic history of the English Lake District. This region has been selected because of its outstanding cultural and environmental value and because it has been extensively and continuously documented since the late-17th century. We outline how natural language processing (NLP) techniques can be integrated with Kew's Plants of the World Online database to enable temporal shifts in plant-naming conventions to be more accurately traced across a heterogeneous corpus of texts published between 1682 and 1904. Through collocate analysis and automated geoparsing techniques, the geographies associated with these plant names are then identified and extracted. Finally, we use GIS to demonstrate the potential of this data set for geo-temporal analysis and for revealing the historical distribution of Lake District flora. In outlining our methodology, this article indicates how the spatial and digital humanities can benefit research both in environmental history and in the environmental sciences more widely.